Atrial fibrillation as a clinical characteristic of arrhythmogenic right ventricular cardiomyopathy: Experience from the Nordic ARVC Registry. (1st January 2020) - Baturova, Maria A.; Haugaa, Kristina H.; Jensen, Henrik K.; Svensson, Anneli; Gilljam, Thomas; Bundgaard, Henning; Madsen, Trine; Hansen, Jim; Chivulescu, Monica; Christiansen, Morten Krogh; Carlson, Jonas; Edvardsen, Thor; et al.
Abstract: Background: Recent studies in arrhythmogenic right ventricular cardiomyopathy (ARVC) patients have drawn attention to atrial fibrillation (AF) as an arrhythmic manifestation of ARVC and as an indicator of atrial involvement in the disease progression. We aimed to assess the prevalence of AF in the Scandinavian cohort of ARVC patients and to evaluate its association with disease clinical manifestations. Methods: Study sample comprised of 293 definite ARVC patients by 2010 Task Force criteria (TFC2010) and 141 genotype-positive family members (total n = 434, 43% females, median age at ARVC diagnosis 41 years [interquartile range (IQR) 28–52 years]). ARVC diagnostic score was calculated as the sum of major (2 points) and minor (1 point) criteria in all categories of the TFC2010. Results: AF was diagnosed in 42 patients (10%): in 41 patients with definite ARVC diagnosis (14%) vs in one genotype-positive family member (1%), p < 0.001. The median age at AF onset was 51 (IQR 38–58) years. The prevalence of AF was related to the ARVC diagnostic score: it significantly increased starting with the diagnostic score 4 (2% in those with score 3 vs 13% in those with score 4, p = 0.023) and increased further with increased diagnostic score (Somer's d value is 0.074, p < 0.001). Conclusion: AF is seen in 14% of definite ARVC patients and is related to the severity of disease phenotype thus suggesting AF being an arrhythmic manifestation of this cardiomyopathy indicating atrial myocardial involvement in the disease progression. Highlights: Atrial fibrillation is common in arrhythmogenic right ventricular cardiomyopathy. Atrial fibrillation prevalence is related to the severity of disease phenotype. Atrial fibrillation is associated with right ventricular structural abnormalities.